2017
DOI: 10.18632/oncotarget.15625
|View full text |Cite
|
Sign up to set email alerts
|

The rs1550117 A>G variant in DNMT3A gene promoter significantly increases non-small cell lung cancer susceptibility in a Han Chinese population

Abstract: In this study, we conducted a case-control study to explore the association between rs1550117 A>G variant of DNMT3A gene promoter and non-small cell lung cancer (NSCLC) susceptibility in a Han Chinese population. The genotyping of rs1550117 A>G variant was performed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and confirmed by sequencing. Allele G of rs1550117 was associated with an increased risk of NSCLC. Moreover, individuals carrying the GG genotypes had a higher risk to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
3
1
1
Order By: Relevance
“…There was no association between these two polymorphisms with the risk of bladder carcinogenesis. This result is in contrast to what has been reported on the DNMT3A rs1550117 variant, which showed a significantly increased risk of developing non-small cell lung cancer (NSCLC) in the Han Chinese population [55]. While Wang et al found that the rs1550117 AG/AA genotype was significantly associated with an increased mortality rate compared with individuals carrying the GG genotype, suggesting that DNMT3a rs1550117 may be a relevant prognostic element for gastric cancer [56].…”
Section: Dnmt3a Rs1550117/dnmt3b Rs1569686contrasting
confidence: 60%
“…There was no association between these two polymorphisms with the risk of bladder carcinogenesis. This result is in contrast to what has been reported on the DNMT3A rs1550117 variant, which showed a significantly increased risk of developing non-small cell lung cancer (NSCLC) in the Han Chinese population [55]. While Wang et al found that the rs1550117 AG/AA genotype was significantly associated with an increased mortality rate compared with individuals carrying the GG genotype, suggesting that DNMT3a rs1550117 may be a relevant prognostic element for gastric cancer [56].…”
Section: Dnmt3a Rs1550117/dnmt3b Rs1569686contrasting
confidence: 60%
“…In contrast to the widely reported high-frequency mutated genes mentioned above, CREBBP (23.1%), KMT2C (16.9%), MUC2 (16.6%), DNMT3A (15.5%), LRP1B (15.5%), MUC4 (15.5%), and CDC27 (15.2%) are currently reported less in the Chinese population, although mutations in DNMT3A and KMT2C have been identified in some studies [ 20 , 33–35 ]. Our results suggest some aspects of the mutational characteristics of these genes in Chinese NSCLC, suggesting functions of these genes in the etiology and treatment of NSCLC.…”
Section: Discussionmentioning
confidence: 88%
“…In some reports, it is described that the frequency of conversion of KRAS in the Chinese is approximately 8% [ 25 , 32 ]. Here, we report a mutation rate of the KRAS gene of 12.8% [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Однако в другом исследовании было показано, что у женщин из популяции Хань, проживающих на юге Китая, генотип DNMT1-290 CT (rs16999593) ассоциирован с повышенным риском развития рака молочной железы [55]. Также для китайской популяции Хань было выявлено, что генотип DNMT3a-786 GG (rs1550117) ассоциирован с предрасположенностью к немелкоклеточному раку легкого [56].…”
Section: успехи молекулярной онкологии / Advancesunclassified